The London Exercise And Pregnant smokers (LEAP) trial: a randomised controlled trial of physical activity for smoking cessation in pregnancy with an economic evaluation - Ussher, Michael; Lewis, Sarah; Aveyard, Paul; Manyonda, Isaac; West, Robert; Lewis, Beth; Marcus, Bess; Riaz, Muhammad; Taylor, Adrian; Barton, Pelham; Daley, Amanda; Essex, Holly; et al. (NIHR Health Technology Assessment Programme, 2015)
BACKGROUND: Smoking during pregnancy is the main preventable cause of poor birth outcomes. Improved methods are needed to help women to stop smoking during pregnancy. Pregnancy provides a compelling rationale for physical activity (PA) interventions as cessation medication is contraindicated or ineffective, and an effective PA intervention could be highly cost-effective.